Micro, Small and Medium Enterprises (MSMEs) Empowerment Strategy in Pondokbungur Village, Purwakarta - Apriani, Farida; Rhiswandi, Rhandi; Apriliani, Rieva; Destiana, Salma (Journal of Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are an important role in driving economic growth. However, in the digital era, MSMEs face the challenge of adapting to ever-evolving technology. The Community Empowerment and Service STIE WIKARA conducted product enrichment and market expansion in Pondokbungur Village, Purwakarta to optimize marketing, sales, and product calculations that are more profitable for MSME entrepreneurs. The results of this KPPM activity provide knowledge for MSME entrepreneurs to manage more attractive packaging, calculate production costs to obtain maximum profit, expand sales networks to seminars for MSME entrepreneurs to promote their products widely through digital and increase public knowledge about the use of digitalization.